Analisis Komparatif Usaha Tani Tebu Varietas BL (Bulu Lawang) dan PS 862 di Desa Sebaung Kecamatan Gending Kabupaten Probolinggo - Alfiansyah, Ela; Lutfi’ah, Hikmatul (KUBIS, 2022)
“Comparative Analysis Of The Cane Farm Varietes Bl (Bulu Lawang) And PS 862 In Sebaung Village, Gending Sub-District, Probolinggo District.” That was taken from a real accurance, that most of farmers are prefer to planting both the varietes with many reason. The purpose of this research is to find out the income ratio of the farm cane farm bussines. Between farm varietes Bl (Bulu lawang) and PS 862. This research also using dercriptive analysis. Dercriptive analysis is a research method to researching a group of human, object, or event. The first instrument that used in this research is question for 30 farmers from each varietes. Method used in this sampling research is simply random sampling. Based on the result of the comparative analysis that using analysis test T Statistic, the result obtained is sig (2 tailed) 1,82 and 1,83. So tahat it can be interpreted if from the result of the analysis Ho : µBL same as NPST ˃0,05 so that ho accepted in the meaning of (There’s no significant differences). While from Ha : µBL is not as same as µPS. So that conclution can be drawn that average income both of them are same of the testing (sta4tistic). Based on the hypotesis know that each farmers varietes Bl (Bulu lawang) and PS 862 have the chance in every harvest. This statement proved fit with the testing that’s been done.